Proinflammatory Effects of C-Peptide in Different Tissues. (11th June 2012) - Vasic, Dusica; Walcher, Daniel
Abstract : Atherosclerosis is well known as an inflammatory disease that can lead to clinical complications such as heart attack or stroke. C-peptide as a cleavage product of proinsulin is in the last few decades known as an active peptide with a number of different effects on microvascular and macrovascular complications in type 2 diabetic patients. Patients with insulin resistance and early type 2 diabetes show elevated levels of C-peptide in blood. Several last findings demonstrated deposition of C-peptide in the vessel wall in ApoE-deficient mice and induction of local inflammation. Besides that, C-peptide has proliferative effects on human mesangial cells. This review discusses recently published proinflammatory effects of C-peptide in different tissues.